Protective Effect of Niosomal Gel of Azadirachta indica against Ulcerative Colitis induced by Dextran Sodium Sulfate (DSS) and Tri Nitro Benzene Sulfonic Acid (TNBS) - Malik, Vikas; Mazumder, Avijit; Das, Saumya (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: This study focuses on finding the protective action of niosomal gel of Azadirachta indica (neem) leaf extract in ulcerative colitis. Materials and Methods: The pharmacological in vivo model conducted here was Dextran Sodium Sulphate (DSS) model of mice colitis and Trinitro Benzene Sulfonic Acid (TNBS) induced ulcerative colitis in rats. Results: In DSS model, the niosomal gel of neem leaf extract at 500 mg/kg dose was found to be significant (**p<0.01). While in TNBS model the significance of niosomal gel containing neem leaf extract at 500 mg/ kg showed highly prominent anticolitic response (***p<0.001). Conclusion: This research proved that niosomal gel of neem leaf extract had prominent effect to reverse the change in body weight and frequency of diarrhoea in treated rats. From the present study it was concluded that niosomal gel of neem leaf extract has prominent anticolitic effect on rats so it may be further use to check its effects clinically.
Keywords: Dextran sodium sulphate; IBD; Irritable Bowel Syndrome (IBS); Trinitro benzene; sulfonic acid